Small RNAs: Analysis and Regulatory Functions - Nellen, Wolfgang; Hammann, Christian (Nucleic Acids and Molecular Biology,, 2006)
In recent years Molecular Biology has experienced an unprecedented revolution by the discovery of functional small RNAs. The number of cellular processes in which non-coding RNAs are involved is growing rapidly and include gene regulation on the transcriptional, post-transcriptional and translational level. To complicate matters, these processes seem to be strongly interconnected on the one hand, and diverse among different organisms on the other. This volume describes strategies for the discovery and validation of small RNAs and provides a snapshot of our current understanding of the different mechanisms triggered by small RNAs.